Thrust allocation logic of dynamically positioned offshore vessel - Jeyasenthil, Ramamoorthy; Dasgupta, Jyotisman (Ships and offshore structures, 2010)
In dynamic positioning (DP) systems, 'thrust allocation' is the problem of determining the thrust and direction of each of the 'n' thrusters in an over-actuated offshore vessel from the desired forces and moment derived in the control law. This is formulated as a non-linear optimisation problem, where the objective is to minimise the use of control effort subject to the constraints, such as actuator rate and power constraints as well as other operational constraints. This paper presents the thrust allocation method for vessels equipped with azimuth thrusters, where the non-linear constrained allocation problem has been solved by the sequential quadratic programming (SQP) method. Simulation results are presented for a semi-submersible, where constraint compliance has been satisfactorily achieved.